1983
DOI: 10.1111/j.1365-2125.1983.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and sleep in insomniac patients.

Abstract: 1 The effects of midazolam (15 and 30 mg p.o.) on the sleep of insomniac patients were assessed by means of polysomnographic recordings. 2 As compared with placebo, 15 mg midazolam significantly increased non-REM sleep while other objective measures of insomnia were only slightly modified. 3 At the 30 mg dose, midazolam significantly decreased total wake time and wake time after sleep onset. On the other hand, total sleep and non-REM sleep time were increased. 4 No development of tolerance was observed followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…In performance studies, midazolam was superior to o x a~e p a m~~ and f l u r a~e p a m ,~~ and generally, a 20-mg dose of midazolam did not cause residual effects 9 hours after ingestion.72. 73 Midazolam was effective in intermediate-term administration to insomniac 69 In addition to intranight rebounds in insomniac pat i e n t~,~' withdrawal of midazolam was followed by rebound insomnia with increased sleep latency, total wake time and wake time after sleep ~n s e t .~~.~' This has not been confirmed in other studies. "…”
Section: Insomniac Patientsmentioning
confidence: 89%
See 1 more Smart Citation
“…In performance studies, midazolam was superior to o x a~e p a m~~ and f l u r a~e p a m ,~~ and generally, a 20-mg dose of midazolam did not cause residual effects 9 hours after ingestion.72. 73 Midazolam was effective in intermediate-term administration to insomniac 69 In addition to intranight rebounds in insomniac pat i e n t~,~' withdrawal of midazolam was followed by rebound insomnia with increased sleep latency, total wake time and wake time after sleep ~n s e t .~~.~' This has not been confirmed in other studies. "…”
Section: Insomniac Patientsmentioning
confidence: 89%
“…In subacute studies in insomniac patients, midazolam, generally in doses of 10-30 mg, shortened sleep latency to sleep stage 2, decreased stage 1 sleep, increased stage 2 sleep, reduced wake time and the number of awakenings after sleep onset and increased total sleep time. The total amount of slowwave sleep decreased and onset of the first REM period was delayed, although the total amount of REM sleep i n c r e a~e d .~~ [69][70][71][72][73] The amount of REM sleep was not affected in all 7n 73 and only a moderate increment in total sleep time was observed after the 15-mg dose. 'jg The effects of 5 mg were those of placebo.…”
Section: Insomniac Patientsmentioning
confidence: 94%
“…Differing opinions on the effect of midazolam on REM sleep are held by a number of other investigators. Monti et al (1983) and Vogel & Vogel (1983) have reported that midazolam slightly decreases REM sleep, while Hauri et al (1983) be unchanged. Others report an increase in REM sleep, especially during the latter part of the night (Gath et al, 1981;A.…”
Section: Subjective Clinical Evaluation Ofefficacy Parametersmentioning
confidence: 96%
“…Nesse sentido, nesta revisão sistemática foram analisados oito estudos científicos relacionados a temática da pesquisa e que corresponderam satisfatoriamente aos critérios de inclusão. Dessa forma, mesmo que os benzodiazepínicos sejam diferentes quanto ao tempo de ação, absorção e potência, como classe, observou-se nesta revisão que eles reduzem a latência do sono, aumentam o tempo total de sono, diminuem os despertares após o início do sono e melhoram a sua qualidade, no entanto, devem ser usados com cautela, priorizando quadros agudos devido ao seu potencial de desenvolvimento de tolerância, abstinência e insônia rebote (KALES et al, 1991;KALES et al,1988;MONTI et al, 1983;MONTI et al,1993).…”
Section: Metodologiaunclassified